Peningkatan Kapasitas Sumber Daya Manusia Melalui Kemampuan Literasi Dan Numerasi Sejak Dini - Akbar Idries, Fahmy; Wahyusari N , Febriani; Ikhsan, Foster; Sutiono PN , Budi (Kreativasi : Journal of Community Empowerment, 2023)
This service program focuses on the importance of literacy and numeracy in the industrial era 4.0 and the efforts made in Indonesia to improve these skills. Literacy is considered a basic need in meeting the needs of human life and developed countries have recognized the importance of literacy as a human right. However, in Indonesia, students' literacy and numeracy abilities are still lacking and have even decreased in recent years. Factors such as the lack of strengthening literacy, the impact of the Covid-19 pandemic, and sub-optimal distance learning have led to a decline in students' abilities. Therefore, the Indonesian government has set literacy as a priority program and strengthened the role of LP Maarif in developing literacy and numeracy. LP Maarif is trying to provide library facilities, develop an integrated curriculum, and provide training to teachers to become agents of literacy development. Hopefully, this effort can help elementary school students build their intelligence and improve their critical, strategic and solutive thinking skills in facing future challenges.